Emergency services management : a research overview - Wankhade, Paresh; Murphy, Peter, 1954- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"An expert guide to contemporary research in the field of emergency services management, this shortform book will help academics, scholars, and practitioners to appreciate the important role and contribution of these services. Contemporary emergency services have been rapidly changing in response to increasing demand, reducing resources, the impact of COVID-19 and the increasingly complex threats to public safety. Academics, practitioners, the emergency services and their key stakeholders all need to have a clear understanding of the changing role and contribution of these services as well as finding ways to improve their management and performance so that policy solutions to new and emerging threats may be efficiently developed and effectively implemented. The book looks at the application of public management theories to emergency services and the development of professionalism within the police, fire and rescue and ambulance services. It examines the increasing need for better collaboration and identifies the nature and extent of the academic and practitioner divide and the research gap between the academic and professional communities in each of the services. This book will be invaluable to researchers, scholars, practitioners and students in the fields of governance, leadership and management, especially those focusing on emergency services and management during crises"--
Emergency Services Management: A Research Overview -- Working Towards Attaining Professional Status -- Collaboration: Issues, Challenges and Opportunities -- Leadership and Culture(s): Still Command and Control? -- The Research-Practice Gaps in Emergency Services -- Conclusion: Collaboration, Not Isolation is the Way Forward.
OCLC-licensed vendor bibliographic record.
Keywords: Emergency management; Municipal services -- Management; Emergency medical services; BUSINESS & ECONOMICS / Management